KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SMAN 2 KALIANDA LAMPUNG SELATAN - Yulianti, Yeti (UNISAN JURNAL, 2024)
This research aims to describe the principal's leadership in improving teacher performance at SMAN 2 Kalianda. This research methodology uses a descriptive qualitative approach, namely information in the form of letters, not numbers. The informants in this research are school principals, teaching staff/teachers. The key informant in this research is the principal because the principal is directly involved every day with the activities of educational staff in the learning process at SMAN 2 Kalianda. The data collection technique is to use interviews, observation and documentation techniques. Test the validity of the data using triangulation techniques. The results of the research show that the principal's leadership in improving teacher performance is good because of the 8 indicators there are six that have been implemented and there are 2 indicators that have not been implemented. The indicators are: providing motivation, work enthusiasm, coaching, discipline, providing consultations, giving awards, making visits. class, showing exemplary attitudes and behavior, building active, creative work, developing the teacher's profession. Meanwhile, teacher performance is quite good, because of the six indicators, four indicators are implemented optimally. The indicators are: preparing learning plans, managing learning activities, establishing interpersonal relationships, carrying out assessments, following up on assessment results, mastering academic studies. Thus, it can be concluded that the leadership of the school principal in improving teacher performance really makes a good contribution to the progress of the quality of learning so that it can encourage the quality of education where the performance of educational staff is the key to success in the world of education.